Homossexualidade e velhice: a dupla estigmatização - Correia, Carlos Alexandre Costa (2009)
This paper deals with the representation of old age and by the look of older gay men. The issue of aging has been discussed around the world, for it is a population in adherence among this population quota is the gay old. The development of this research is presented by analyzing and interpreting the representations of the speech of older gay men. Through a qualitative methodology. The research seeks to know a little of this old world of homosexuals, new social arrangements, as well as new emotional relationships outside heterosexual dominant group in society. Understand how the prejudice and stigma in relation to group and described and analyzed. Seek to understand their offices on aging, family, sexual orientation in order to meet this social group. The analysis of the data were grouped into categories testimonies that are recurring themes in the discourse of the subject, and his analysis was based on the theoretical